The economics of higher purpose : eight counterintuitive steps for creating a purpose-driven organization - Quinn, Robert E.; Thakor, Anjan V. (Berrett-Koehler Publishers, 2019)
"Two distinguished scholars offer eight steps to help organizations discover and embrace an authentic higher purpose--something that will dramatically improve every aspect of any enterprise, including the bottom line. What does a lofty notion like purpose have to do with business basics like the bottom line? Robert E. Quinn and Anjan J. Thakor say pretty much everything. Leaders and managers are taught that employees are self-interested and work resistant, so they create systems of control to combat these expectations. Workers resent these systems, and performance suffers. To address the performance issues, managers double down on the coercion, creating a vicious cycle and a self-fulfilling prophecy. But there is a better way. Quinn and Thakor show that when an authentic higher purpose permeates business strategy and decision-making, the cycle is broken. Employers and employees see themselves as working together toward an inspiring goal, not just trying to hit quarterly targets. They fully engage, become proactive contributors, and, ironically, easily exceed those quarterly targets. Based on their widely acclaimed Harvard Business Review article, Quinn and Thakor offer eight sometimes surprising steps for shifting from a transaction-oriented mind-set focused on constraints to a purpose-oriented mind-set focused on possibility. This iconoclastic book will help any organization discover its authentic purpose and weave it into the fabric of everything it does, leading to unprecedented levels of personal satisfaction, service and product innovation, and economic growth"--